Comparison of Dectomax® and Valbazen® on feedlot steer performance and carcass traits - Christopher, J.A.; Marston, T.T.; Brethour, J.R.; Stokka, Gerald L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred thirty-nine steers were fed at the K-State Agricultural Research Center– Hays to compare the effects of different deworming agents on feedlot performance and carcass traits. This experiment consisted of two replications with steers being fed a finishing diet based on ground sorghum-grain for approximately 100 days. Before the start of each replication, steers were commingled for approximately 30 days and then stratified into high- and low-marbling groups via ultrasound measurements. Within each marbling group, steers were randomly allotted to a treatment. Treatments consisted of an oral application of Valbazen® or a subcutaneous injection of Dectomax® dewormer. Dosages of deworming products followed label instructions. At time of treatment and 12 days later, fecal grab samples were analyzed for indications of internal parasite infestation. Both deworming agents reduced fecal egg counts. Feedlot performance, as measured by daily gain and feed efficiency, was unaffected by treatment. Dectomax®-treated cattle had greater marbling scores and had a greater percentage of carcasses grading USDA Choice or greater than did cattle given Valbazen®. Steers receiving Dectomax® had thicker backfat and greater Yield Grade measurements than did the Valbazen®-treated steers. Other carcass traits were similar between treatment groups. Our data indicate that both Dectomax® and Valbazen® deworming agents can effectively reduce internal parasites, but feedlot steers given Dectomax® had more intramuscular and external fat deposition.
Keywords: Beef; Dectomax®; Valbazen®; Steer performance and carcass traits